Sandwich-structure flexible transparent conductive electrode and preparation method thereof
By depositing flexible transparent conductive electrodes with MXene/AgNWs/MXene sandwich structure on a flexible transparent substrate, the problems of low coverage, high junction resistance and large surface roughness of AgNWs films in flexible optoelectronic devices are solved, and high conductivity, low surface roughness and good mechanical properties are achieved.
Patent Information
- Application Number
- CN202411656288.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-28
AI Technical Summary
When preparing flexible transparent conductive electrodes, the existing AgNWs films have problems such as low coverage, high junction resistance and large surface roughness, which limits their application in optoelectronic devices.
Using a sandwich structure based on the hybridization of MXene and AgNWs, the MXene/AgNWs/MXene flexible transparent conductive electrode was formed by depositing the bottom MXene nanosheet film, the AgNWs film and the top MXene nanosheet film on a flexible transparent substrate in sequence, and applying mechanical pressure treatment.
It effectively solves the problems of low coverage, high junction resistance and large surface roughness of AgNWs films, improves conductivity, reduces surface roughness, and enhances mechanical flexibility, stability and adhesion.
Smart Images

Figure CN119730579A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of semiconductor optoelectronic technology and relates to a flexible transparent conductive electrode, in particular to a flexible transparent conductive electrode applicable to nano optoelectronic devices such as flexible organic light emitting diodes and solar cells and a preparation method thereof. Background Art
[0002] The flexible electronics industry has developed rapidly in recent years. Flexible nano-photoelectric devices such as flexible organic light-emitting diodes (OLEDs), flexible solar cells, and flexible sensing and detection devices have gradually entered the market, changing people's production and life. The growing demand for flexible electronic products promotes the continuous development of society.
[0003] Flexible transparent conductive electrodes are an important component of flexible nano-photoelectric devices and the key to realizing flexible nano-photoelectric devices. Indium tin oxide (ITO) is widely used as an electrode for optoelectronic devices due to its high transmittance and good conductivity. However, the inherent brittleness of ITO makes it unsuitable for use in flexible optoelectronic devices, which greatly limits the development of flexible optoelectronic devices. In order to develop flexible transparent conductive electrodes that can replace ITO, researchers have done a lot of research in this regard and proposed a variety of strategies and solutions for constructing flexible transparent conductive electrodes. For example, it is proposed to use silver nanowires (AgNWs), carbon nanotubes and two-dimensional (quasi-two-dimensional) materials to construct high-performance flexible transparent conductive electrodes. Among these materials, AgNWs has become a material with great potential for the development of flexible transparent conductive electrodes due to its excellent properties such as high conductivity and transmittance, good film forming properties and outstanding mechanical flexibility.
[0004] In the process of controllable synthesis of AgNWs, in order to control the aspect ratio of AgNWs, a layer of non-conductive polymer material polyvinyl pyrrolidone (PVP) is coated on the surface of AgNWs through solution film-forming processes such as spin coating, spray coating, and scraping. When AgNWs conductive film is prepared by solution film-forming process, a large number of AgNWs / AgNWs connection points will be formed in the film, and the intersecting AgNWs cannot be fused together at the connection points, resulting in the inability to form an effective AgNWs grid, making the overall film conductivity very poor, limiting its application in optoelectronic devices.
[0005] Not only does the presence of non-conductive PVP on the surface of AgNWs make the high contact resistance at the AgNWs / AgNWs junction unfavorable for the formation of highly conductive films, but the high bundling of the AgNWs / AgNWs junction also makes the overall film have a very high surface roughness, further limiting its application in nano-photoelectric devices. On the other hand, AgNWs prepared by conventional solution film-forming processes often have poor adhesion to the substrate, which restricts the mechanical flexibility and stability of the conductive film.
[0006] Post-processing (brazing, laser welding, capillary welding, etc.) of the AgNWs film prepared by the solution processing method can achieve effective fusion and welding of the AgNWs / AgNWs connection points of the thin film, form a conductive network, and improve the conductivity of the AgNWs flexible electrode. However, the problems of surface roughness and adhesion to the substrate cannot be effectively solved.
[0007] Kim et al. J. Sci: Adv Mater Devices . 2021, 6 , 372.) By depositing another layer of conductive polymer PEDOT:PSS (poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate)) film on the AgNWs film, the vacant parts of the AgNWs grid can be effectively filled, the film flatness can be improved, and the electrode surface roughness can be reduced. However, the inherent acidity and relatively poor stability of PEDOT:PSS restrict the development of highly stable and adhesive electrodes.
[0008] Titanium carbide (Ti3C2Tx-MXene, MXene) is a new type of two-dimensional transition metal carbide with a layered structure, which has metallic conductivity, high optical transparency, flexibility and high chemical stability. In addition, MXene also has abundant surface termination groups, such as oxygen (-O), hydroxyl (-OH) and fluorine (-F), etc. The presence of these groups makes MXene hydrophilic (Q.Lu., et al. Chem. Eng. J . 2022, 450 , 138439.), which is beneficial to the preparation of high-quality conductive films.
[0009] Through novel structural design and simple preparation process, the development of AgNWs flexible transparent conductive electrodes with high conductivity, low surface roughness, high mechanical flexibility and stability is achieved, which is of great significance to promoting the development of flexible nano-photoelectric devices. Summary of the invention
[0010] The purpose of the present invention is to provide a sandwich structure flexible transparent conductive electrode based on hybridization of MXene and silver nanowires and a preparation method thereof, so as to be better applied in the preparation of flexible organic light-emitting diode devices.
[0011] The sandwich structure flexible transparent conductive electrode described in the present invention is a composite film formed by sequentially depositing a bottom MXene nanosheet film, an AgNWs film and a top MXene nanosheet film on a flexible transparent substrate through a solution film forming process, and the composite film is subjected to mechanical pressure treatment to obtain a sandwich structure MXene / AgNWs / MXene flexible transparent conductive electrode.
[0012] The flexible transparent conductive electrode of the present invention has no special requirements for the flexible transparent substrate, and various conventional materials that can be used as flexible films can be used, including but not limited to any one of flexible, transparent plastic films such as polyethylene terephthalate (PET), low-density polyethylene (LDPE), polyethylene naphthalate (PEN), polyimide (PI) or polydimethylsiloxane (PDMS).
[0013] Preferably, the flexible transparent substrate described in the present invention is a PET film.
[0014] In the present invention, the MXene can be prepared according to any method reported in the literature. For example, by chemical liquid phase etching, carbon aluminum titanium (Ti3AlC2) powder is added to a mixed solution of lithium fluoride (LiF) and hydrochloric acid (HCl) for etching, and then centrifuged and washed repeatedly until the pH value is 6, and then deionized water is added for ultrasonic treatment, and MXene nanosheets are obtained by centrifugation.
[0015] Specifically, the mechanical pressure treatment in the present invention is preferably to apply an external pressure of 1 to 50 MPa to the composite film.
[0016] Furthermore, the present invention also provides a method for preparing the sandwich structure flexible transparent conductive electrode, comprising:
[0017] S1: depositing a MXene dispersion on a flexible transparent substrate, and annealing to construct an underlying MXene nanosheet film, wherein the annealing temperature is higher than the sublimation temperature of the MXene dispersion;
[0018] S2: Continue to deposit the AgNWs dispersion on the bottom MXene nanosheet film, and anneal to form an AgNWs film, wherein the annealing temperature is higher than the sublimation temperature of the AgNWs dispersion;
[0019] S3: Continue to deposit MXene dispersion on the AgNWs film, and perform annealing to construct a top MXene nanosheet film, wherein the annealing temperature is higher than the sublimation temperature of the MXene dispersion;
[0020] S4: Applying a pressure of 1 to 50 MPa to the composite film prepared above for mechanical pressure treatment to prepare a sandwich structure MXene / AgNWs / MXene flexible transparent conductive electrode with excellent comprehensive performance.
[0021] Among them, the present invention preferably deposits the MXene dispersion or the AgNWs dispersion by solution spin coating or solution spraying.
[0022] Furthermore, the annealing treatment time in the present invention is preferably 1 to 60 minutes.
[0023] The above method of the present invention can be used to construct a high-quality bottom MXene nanosheet film, an AgNWs film and a top MXene nanosheet film, and the transmittance of the film is greater than 70%.
[0024] Furthermore, the MXene dispersion or AgNWs dispersion described in the present invention is a dispersion with good dispersion effect obtained by preparing solvents with similar polarity to MXene or AgNWs. These solvents with similar polarity to MXene or AgNWs can be a single solvent or a mixed solvent composed of two or more solvents. The purpose is to obtain high-quality MXene or AgNWs films.
[0025] The sandwich structure MXene / AgNWs / MXene flexible transparent conductive electrode of the present invention can first be used as an electrode of a flexible OLEDs device, and can also be used as an electrode in other flexible nano-photoelectric devices such as solar cells and photoelectric detection devices, and has great application prospects.
[0026] Furthermore, the sandwich structure flexible transparent conductive electrode of the present invention can be used as both an anode material and a cathode material of an OLED device.
[0027] Specifically, after the sandwich structure flexible transparent conductive electrode prepared by the present invention is patterned with anhydrous ethanol, it can be used as an anode material or a cathode material, and other organic functional layer materials and cathode materials (or anode materials) can be directly vacuum evaporated to prepare a flexible OLEDs device.
[0028] The present invention forms a flexible transparent conductive electrode with a sandwich structure by sequentially depositing a bottom MXene nanosheet film, an AgNWs film and a top MXene nanosheet film on a flexible transparent substrate and applying mechanical pressure, wherein the bottom and top MXene nanosheet films can fill the gaps in the AgNWs grid, and wrap and weld the AgNWs / AgNWs contacts, effectively promoting the formation of a conductive network, reducing the AgNWs / AgNWs contact resistance, and making the electrode have excellent conductivity; at the same time, the stable MXene nanosheet film can also inhibit the oxidation of AgNWs, and improve the thermal stability and chemical stability of the electrode; a large number of oxygen-containing functional groups on the surfaces of the bottom and top MXene nanosheet films form hydrogen bonds with each other on the one hand to improve the mutual combination with AgNWs, and on the other hand form hydrogen bonds with the flexible substrate rich in oxygen-containing functional groups, thereby improving the adhesion between the conductive electrode and the flexible substrate; finally, under the action of mechanical pressure, the roughness of the flexible transparent conductive electrode is greatly reduced, and the AgNWs / AgNWs contacts are further welded, so that the AgNWs are partially embedded in the flexible substrate.
[0029] The present invention is based on the hybridization of MXene and AgNWs, which effectively solves the problems of low coverage, high node resistance and large roughness of the existing AgNWs film, further improves the conductivity of the flexible transparent conductive electrode, reduces the surface roughness, and improves the mechanical flexibility, stability and adhesion. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a process flow chart for preparing sandwich-structured flexible transparent conductive electrodes.
[0031] Figure 2 This is the X-ray diffraction pattern of the MXene nanosheets prepared in Example 1.
[0032] Figure 3 This is a transmission electron microscope image of the MXene nanosheets prepared in Example 1.
[0033] Figure 4 are the static water contact angles of PET substrate (a), UV-treated PET substrate (b), and MXene film (c).
[0034] Figure 5 These are the resistance test results of flexible transparent conductive electrodes with different structures.
[0035] Figure 6 This is a scanning electron microscope image of AgNWs and sandwich structure MXene / AgNWs / MXene flexible transparent conductive electrode.
[0036] Figure 7 These are the atomic force images of AgNWs, MXene / AgNWs / MXene films and sandwich structure MXene / AgNWs / MXene flexible transparent conductive electrodes.
[0037] Figure 8 This is a test chart of the bending stability of different flexible transparent conductive electrodes.
[0038] Fig. 9 These are the oxidation and adhesion test diagrams of different flexible transparent conductive electrodes.
[0039] Fig.10 The normalized electroluminescence spectrum, current density-voltage-brightness, external quantum efficiency-brightness and current efficiency-brightness characteristic curves of the green phosphorescent OLEDs device prepared in Application Example 2 are shown.
[0040] Fig.11 This is a single carrier charge balance analysis diagram of the green phosphorescent OLEDs device in Application Example 2; the FTCEs in the figure are flexible transparent conductive electrodes.
[0041] Fig.12The normalized electroluminescence spectrum, current density-voltage-brightness, external quantum efficiency-brightness and current efficiency-brightness characteristic curves of the red phosphorescent OLEDs device prepared in Application Example 3 are shown.
[0042] Fig.13 This is a single carrier charge balance analysis diagram of the red phosphorescent OLEDs device in Application Example 3. Implementation
[0043] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solution of the present invention so that those skilled in the art can well understand and utilize the present invention, rather than limiting the scope of protection of the present invention.
[0044] The production processes, experimental methods or detection methods involved in the following embodiments of the present invention, unless otherwise specified, are all conventional methods in the prior art, and their names and / or abbreviations are all conventional names in the field, and are very clear and unambiguous in the relevant application fields. Technicians in the field can understand the conventional process steps based on the names and apply the corresponding equipment to implement them according to conventional conditions or the conditions recommended by the manufacturer.
[0045] The various instruments, equipment, raw materials or reagents used in the embodiments of the present invention are not particularly limited in terms of their sources, and are all conventional products that can be purchased through regular commercial channels, or can be prepared according to conventional methods well known to those skilled in the art.
[0046] The preparation method of the sandwich structure MXene / AgNWs / MXene flexible transparent conductive electrode involved in the embodiment of the present invention is as follows:
[0047] 1. Synthesis of MXene nanosheets
[0048] 1. First, dissolve LiF in a certain concentration of HCl and stir to fully dissolve it;
[0049] 2. Slowly add Ti3AlC2 into the above solution and stir for no less than 24 hours;
[0050] 3. After the stirring reaction is completed, centrifuge and wash repeatedly with deionized water until the pH is close to 6;
[0051] 4. Remove the supernatant, leaving the clay-like precipitate, add deionized water, and ultrasonically treat for 2 hours under nitrogen atmosphere to obtain the initial MXene nanosheet dispersion;
[0052] 5. Finally, the dispersion was centrifuged at 3500 rpm for 15 min, and the supernatant was taken to obtain the final MXene nanosheet dispersion for film formation.
[0053] 2. Press Figure 1 Process flow for preparing sandwich structure MXene / AgNWs / MXene flexible transparent conductive electrode
[0054] 1. The PET substrate was ultrasonically cleaned with deionized water, acetone and isopropanol for 15 minutes, and then dried in a constant temperature drying oven at 60°C to obtain a clean and dust-free PET substrate;
[0055] 2. Take out the PET substrate from the constant temperature drying oven, put it into the UV box, and irradiate it with UV light for 10 minutes to further remove the residual organic matter on the surface of the PET substrate and improve the wettability of the PET substrate;
[0056] 3. Spin-coat 0.2-1.0 mg / ml of MXene nanosheet dispersion on the UV-ozone treated PET substrate at a speed of 2000 rpm, place it in a glove box, and anneal it at 120°C. After the solvent is completely evaporated, the bottom MXene nanosheet film is obtained;
[0057] 4. Spin-coat a 1.0-1.8 mg / ml isopropanol to water ratio of (5:5) to (9:1) AgNWs solution on the bottom MXene nanosheet film at a speed of 1000-5000 rpm, place it in a glove box, anneal it at 120°C, and after the solvent is completely evaporated, form a MXene / AgNWs film;
[0058] 5. Spin-coat 0.2-1.0 mg / ml of MXene nanosheet dispersion on the MXene / AgNWs film again at a speed of 2000 rpm, place it in a glove box, and anneal it at 120°C. After the solvent is completely evaporated, a MXene / AgNWs / MXene composite film is formed;
[0059] 6. Place the MXene / AgNWs / MXene composite film between two mirror-like press sheets and apply a pressure of 20 MPa to obtain a sandwich structure MXene / AgNWs / MXene flexible transparent conductive electrode.
[0060] The OLED device involved in the embodiment of the present invention is specifically prepared by the following high vacuum thermal evaporation process:
[0061] 1. Conductive film cavity
[0062] Dip a cotton swab in anhydrous ethanol to pattern the prepared flexible transparent conductive electrode, quickly place it on the mask, and introduce the mask into the vacuum evaporation chamber;
[0063] 2. Vacuum the equipment
[0064] Turn on the power supply, mechanical pump, and molecular pump of the high vacuum coating machine in sequence to evacuate the vacuum chamber;
[0065] 3. Thermal Evaporation Preparation of OLEDs
[0066] When the vacuum degree in the high vacuum coating machine chamber is lower than 5×10 -4 At 100 Pa, the thermal evaporation sources containing hole and electron injection layer materials, hole and electron transport layer materials and luminescent materials in the cavity are heated separately, and various functional layers are thermally deposited on the flexible transparent conductive electrode in sequence according to the designed device structure. The mask plate containing the flexible transparent conductive film is rotated to align the mask position for depositing the aluminum cathode with the flexible transparent conductive film, and the thermal evaporation source containing the aluminum wire is heated to deposit the aluminum cathode, and finally a complete OLED is prepared.
[0067] During the device preparation process, the evaporation rate of the material and the thickness of the evaporated film layer are monitored by a quartz crystal frequency meter connected outside the vacuum chamber. Among them, the evaporation rates of various organic functional materials, LiF and aluminum are about 1Å / s, 0.1Å / s and 3Å / s respectively. Finally, the overlapping part of the patterned transparent anode and the aluminum cathode is used as the effective light-emitting area of the device, and the effective light-emitting area of the device is 3mm×3mm.
[0068] The prepared OLEDs device was taken out from the vacuum chamber, and the current density, current efficiency and brightness of the device were obtained using a computer-controlled BM-7A photometer and a Keithley 2400 source digital source meter. The device performance, such as the electroluminescence spectrum, color coordinates and color rendering index of the device at different voltages, was tested using a computer-controlled Spectra Scan PR655 spectroradiometer. Example
[0069] Example 1
[0070] Weigh 3.2 g of LiF and dissolve it in 60 ml of 9 M HCl solution. Stir for 10 min to fully dissolve it.
[0071] 2 g of Ti3AlC2 was slowly added to the above solution within 15 min, and stirred at 35°C for 24 h. After the reaction was completed, the solution was repeatedly centrifuged and washed with deionized water at 3500 rpm until the pH value of the centrifuge was close to 6.
[0072] The clay-like precipitate was collected, added with deionized water, and ultrasonically treated for 2 h under a nitrogen atmosphere to obtain an initial MXene nanosheet dispersion.
[0073] The initial MXene nanosheet dispersion was centrifuged at 3500 rpm for 15 min, and the supernatant was taken to obtain the final MXene nanosheet dispersion for film formation.
[0074] Figure 2 In the XRD spectrum, the strongest peak at 6.8° corresponds to the (002) crystal plane of MXene, and there is no characteristic diffraction peak of Al, indicating that MXene nanosheets have been successfully synthesized.
[0075] from Figure 3 From the transmission electron microscopy image of MXene nanosheets, it can be seen that MXene is in smooth and uniform lamellar form with a lateral size of 1 to 2 μm, a smooth surface and clear edges.
[0076] Example 2
[0077] The 1.97 cm × 1.97 cm PET substrate was ultrasonically cleaned with deionized water, acetone and isopropanol for 15 min in turn, and dried in a constant temperature drying oven at 60°C to obtain a dry, clean and dust-free PET substrate. It was then placed in a UV box and irradiated with UV light for 10 min to further remove residual organic matter on the surface and improve the wettability of the PET substrate.
[0078] AgNWs were added to a mixed solution of isopropanol and water in a volume ratio of 7:3 to prepare an AgNWs dispersion with a concentration of 1.6 mg / ml. 60 μl of the dispersion was spin-coated on the above-treated PET substrate at a speed of 2000 rpm, placed in a glove box, and annealed at 120°C for 15 min until the solvent was completely evaporated to form an AgNWs film, thereby preparing a flexible transparent electrode, recorded as AgNWs.
[0079] Example 3
[0080] The 1.97 cm × 1.97 cm PET substrate was ultrasonically cleaned with deionized water, acetone and isopropanol for 15 min in turn, and dried in a constant temperature drying oven at 60°C to obtain a dry, clean and dust-free PET substrate. It was then placed in a UV box and irradiated with UV light for 10 min to further remove residual organic matter on the surface and improve the wettability of the PET substrate.
[0081] AgNWs were added to a mixed solution of isopropanol and water in a volume ratio of 7:3 to prepare an AgNWs dispersion with a concentration of 1.6 mg / ml. 60 μl of the dispersion was spin-coated on the above-treated PET substrate at a speed of 2000 rpm, placed in a glove box, and annealed at 120°C for 15 min until the solvent was completely evaporated to form an AgNWs film.
[0082] The AgNWs film was placed between two mirror-smooth flat plates, and pressed at a pressure of 20 MPa for 15 seconds to prepare a flexible transparent conductive electrode, which was recorded as P-AgNWs.
[0083] Example 4
[0084] The 1.97 cm × 1.97 cm PET substrate was ultrasonically cleaned with deionized water, acetone and isopropanol for 15 min in turn, and dried in a constant temperature drying oven at 60°C to obtain a dry, clean and dust-free PET substrate. It was then placed in a UV box and irradiated with UV light for 10 min to further remove residual organic matter on the surface and improve the wettability of the PET substrate.
[0085] The concentration of the MXene nanosheet dispersion prepared in Example 1 was adjusted to 0.6 mg / ml, 120 μl was taken, and spin-coated on the above-treated PET substrate at a speed of 2000 rpm, placed in a glove box, and annealed at 120° C. for 15 min. After the deionized water was completely evaporated, a MXene film was formed.
[0086] AgNWs were added to a mixed solution of isopropanol and water in a volume ratio of 7:3 to prepare an AgNWs dispersion with a concentration of 1.6 mg / ml. 60 μl was taken and spin-coated on the above-mentioned MXene film at a speed of 2000 rpm. The film was annealed at 120°C in a glove box for 15 min until the solvent was completely evaporated to form a MXene / AgNWs film.
[0087] The MXene / AgNWs film was placed between two mirror-smooth flat plates and pressed at a pressure of 20 MPa for 15 seconds to prepare a flexible transparent conductive electrode, which was recorded as MXene / AgNWs.
[0088] Example 5
[0089] The 1.97 cm × 1.97 cm PET substrate was ultrasonically cleaned with deionized water, acetone and isopropanol for 15 min in turn, and dried in a constant temperature drying oven at 60°C to obtain a dry, clean and dust-free PET substrate. It was then placed in a UV box and irradiated with UV light for 10 min to further remove residual organic matter on the surface and improve the wettability of the PET substrate.
[0090] AgNWs were added to a mixed solution of isopropanol and water in a volume ratio of 7:3 to prepare an AgNWs dispersion with a concentration of 1.6 mg / ml. 60 μl of the dispersion was spin-coated on the above-treated PET substrate at a speed of 2000 rpm, placed in a glove box, and annealed at 120°C for 15 min until the solvent was completely evaporated to form an AgNWs film.
[0091] The concentration of the MXene nanosheet dispersion prepared in Example 1 was adjusted to 0.6 mg / ml, 120 μl was taken, and spin-coated on the above-mentioned AgNWs film at a speed of 2000 rpm, placed in a glove box, and annealed at 120° C. for 15 min. After the deionized water was completely evaporated, an AgNWs / MXene film was formed.
[0092] The AgNWs / MXene film was placed between two mirror-smooth flat plates and pressed at a pressure of 20 MPa for 15 seconds to prepare a flexible transparent conductive electrode, which was recorded as AgNWs / MXene.
[0093] Example 6
[0094] The 1.97 cm × 1.97 cm PET substrate was ultrasonically cleaned with deionized water, acetone and isopropanol for 15 min in turn, and dried in a constant temperature drying oven at 60°C to obtain a dry, clean and dust-free PET substrate. It was then placed in a UV box and irradiated with UV light for 10 min to further remove residual organic matter on the surface and improve the wettability of the PET substrate.
[0095] The concentration of the MXene nanosheet dispersion prepared in Example 1 was adjusted to 0.6 mg / ml, 120 μl was taken, and spin-coated on the above-treated PET substrate at a speed of 2000 rpm, placed in a glove box, and annealed at 120° C. for 15 min. After the deionized water was completely evaporated, a MXene film was formed.
[0096] AgNWs were added to a mixed solution of isopropanol and water in a volume ratio of 7:3 to prepare an AgNWs dispersion with a concentration of 1.6 mg / ml. 60 μl was taken and spin-coated on the above-mentioned MXene film at a speed of 2000 rpm. The film was annealed at 120°C in a glove box for 15 min until the solvent was completely evaporated to form a MXene / AgNWs film.
[0097] 120 μl of 0.6 mg / ml MXene nanosheet dispersion was spin-coated again on the MXene / AgNWs film formed above at a rotation speed of 2000 rpm, and annealed at 120° C. in a glove box to form a MXene / AgNWs / MXene film.
[0098] The MXene / AgNWs / MXene film was placed between two upper and lower mirror-smooth flat plates, and pressed at a pressure of 20 MPa for 15 seconds to prepare the flexible transparent conductive electrode with a sandwich structure of the present invention, which was recorded as MXene / AgNWs / MXene.
[0099] The pressure will not damage the nanostructure of the film. To avoid the introduction of other impurities during pressing, the two mirror-smooth plates need to be wiped with ethanol each time they are used and then used after they are completely dry.
[0100] The cleaned and dried PET substrate and the PET substrate treated with UV light were used as controls to test the change in the static water contact angle of the formed MXene film. The results are as follows: Figure 4 .
[0101] Figure 4 The static water contact angle shows that although the contact angle of the PET substrate can be reduced from 65° to 40° by UV-ozone treatment for 10 minutes, the water contact angle is further reduced to 32.5° after spin coating the MXene dispersion to form a thin film. This shows that the formation of the underlying MXene film can not only fill the gaps on the surface of the PET substrate, but also inhibit the agglomeration of AgNWs, which is conducive to the formation of a uniformly distributed AgNWs conductive network.
[0102] This can be further Figure 5 The test results of different electrode resistances were verified.
[0103] Figure 5 The resistance of AgNWs, P-AgNWs, MXene / AgNWs, AgNWs / MXene and MXene / AgNWs / MXene flexible transparent conductive electrodes prepared in the above Examples 2 to 6 are given. Among them, the resistance of P-AgNWs treated with mechanical pressing is significantly lower than that of AgNWs, proving that after applying mechanical pressure, the connection between AgNWs is tighter and the resistance is further reduced. Furthermore, the resistance of MXene / AgNWs with an underlying MXene film is lower than that of P-AgNWs, indicating that the underlying MXene film constructs a basic conductive path, and the reduction in its contact angle enables AgNWs to better adhere to the substrate, further reducing the resistance. The resistance of AgNWs / MXene and MXene / AgNWs / MXene, which are spin-coated with a top MXene film, is further reduced, which is based on the conductivity of MXene itself, which provides an additional conductive path and connects the nodes of AgNWs, so the resistance is gradually reduced.
[0104] Figure 6 In the scanning electron microscope image, compared with the pure AgNWs on the left, in the MXene / AgNWs / MXene flexible transparent conductive electrode on the right, it can be clearly seen that the bottom MXene film and the top MXene film fill the gaps of the AgNWs, improve the coverage of the AgNWs, and provide additional conductive paths. At the same time, the MXene nanosheet structure is not damaged by the applied pressure, and the connection between the AgNWs is tighter.
[0105] Furthermore, through Figure 7From the two-dimensional atomic force image, it can be seen that the surface roughness of the pure AgNWs film (a) reaches 25.03nm. After the double-layer MXene, the surface roughness of the formed MXene / AgNWs / MXene film (b) is reduced to 22.83nm. After mechanical pressing, the roughness is further reduced. Under the synergistic effect of MXene and mechanical pressing, the surface roughness finally reaches 7.98nm in (c). The lower roughness reflects that the film surface is smoother and more suitable for the preparation of flexible OLEDs devices. When the roughness is large, the irregularities and protrusions on the film surface can easily pierce the light-emitting layer, causing the optoelectronic device to short-circuit.
[0106] Example 7
[0107] The concentration of the MXene nanosheet dispersion prepared in Example 1 was adjusted to 1.0 mg / ml, 80 μl was taken, and spin-coated at 3000 rpm on the PET substrate treated according to the method of Example 2, placed in a glove box, and annealed at 130° C. for 10 min. After the deionized water was completely evaporated, a MXene film was formed.
[0108] AgNWs were added to a mixed solution of isopropanol and water in a volume ratio of 9:1 to prepare an AgNWs dispersion with a concentration of 1.2 mg / ml. 100 μl was taken and spin-coated on the above-mentioned MXene film at a speed of 1500 rpm. The film was annealed at 130°C in a glove box for 10 min until the solvent was completely evaporated to form a MXene / AgNWs film.
[0109] 80 μl of 1.0 mg / ml MXene nanosheet dispersion was spin-coated again on the MXene / AgNWs film formed above at a rotation speed of 3000 rpm, and annealed at 130° C. in a glove box to form a MXene / AgNWs / MXene film.
[0110] The MXene / AgNWs / MXene film was placed between two mirror-smooth flat plates and pressed at a pressure of 15 MPa for 20 seconds to prepare a sandwich-structured MXene / AgNWs / MXene flexible transparent conductive electrode.
[0111] Example 8
[0112] The concentration of the MXene nanosheet dispersion prepared in Example 1 was adjusted to 0.4 mg / ml, 200 μl was taken, and spin-coated at 2000 rpm on the PET substrate treated according to the method of Example 2, placed in a glove box, and annealed at 100° C. for 20 min. After the deionized water was completely evaporated, a MXene film was formed.
[0113] AgNWs were added to a mixed solution of isopropanol and water in a volume ratio of 6:4 to prepare an AgNWs dispersion with a concentration of 1.0 mg / ml. 120 μl was taken and spin-coated on the above-mentioned MXene film at a speed of 1000 rpm. The film was annealed at 100°C in a glove box for 20 min until the solvent was completely evaporated to form a MXene / AgNWs film.
[0114] 200 μl of 0.4 mg / ml MXene nanosheet dispersion was spin-coated again on the MXene / AgNWs film formed above at a rotation speed of 2000 rpm, and annealed at 100° C. in a glove box to form a MXene / AgNWs / MXene film.
[0115] The MXene / AgNWs / MXene film was placed between two mirror-smooth flat plates and pressed at a pressure of 22 MPa for 10 seconds to prepare a sandwich-structured MXene / AgNWs / MXene flexible transparent conductive electrode.
[0116] Application Example 1
[0117] The film stability properties of the AgNWs, P-AgNWs, MXene / AgNWs, AgNWs / MXene and MXene / AgNWs / MXene flexible transparent conductive electrodes prepared in Examples 2 to 6 were tested respectively, including bending stability, oxidation resistance and adhesion, and a commercial flexible PET-ITO conductive film (South China Xiangcheng Technology Co., Ltd., resistance <40Ω) was used as a control.
[0118] Among them, the bending stability test was carried out according to Chen et al. ( J. Mater. Chem. C , 2022, 10 , 8625.) The test method reported in the paper was used to test the bending times-resistance change rate (a) and curvature radius-resistance change rate (b) of the film.
[0119] First, when the bending radius is 5 mm, the resistance change rate (R / R0) of the flexible transparent conductive electrode under different bending cycles is investigated. Figure 8 As shown in (a), as the number of bending times increases, the resistance of ITO increases rapidly, while the resistance of various flexible transparent conductive electrodes of the present invention, including MXene / AgNWs / MXene, remains almost unchanged after being bent 1000 times.
[0120] and then, Figure 8(b) shows the resistance change rate of various flexible transparent conductive electrodes at different bending radii. Similarly, the resistance of various flexible transparent conductive electrodes such as MXene / AgNWs / MXene remains stable and hardly changes within the bending radius of 2 to 10 mm, but the resistance of ITO increases rapidly as the bending radius decreases.
[0121] Oxidation test was performed according to Qin et al. ACS Appl. Mater. Interfaces , 2022, 14 , 38021.) reported method, different films were placed in a 60°C oven to test the change trend of film resistance over time; the adhesion test was performed according to Du et al. ( Adv. Funct. Mater , 2024, 34 , 2401567) method to test the change of film resistance with the number of times the 3M tape is peeled off.
[0122] from Fig. 9 As shown in (a), when different films are placed in a 60°C oven, the resistance of AgNWs, P-AgNWs and MXene / AgNWs films gradually increases with time, proving that the surface AgNWs are oxidized to a certain extent. However, under the protection of the top layer MXene, the oxidation of AgNWs is greatly limited for AgNWs / MXene and MXene / AgNWs / MXene films, which enhances the stability of the films. When placed for 600 hours, the resistance change rate over time is the lowest.
[0123] Fig. 9 (b) shows the resistance change of different films after 3M tape peeling cycles. The AgNWs without any treatment were peeled off only once. Under the action of mechanical pressure, the adhesion of various films to the substrate was greatly improved, but it is obvious that the resistance change of P-AgNWs is still high. The adhesion performance of various films after adding the bottom layer MXene is similar. After 20 cycles of peeling, the resistance change of the sandwich structure flexible transparent conductive electrode is the lowest, and the adhesion of AgNWs to the substrate is greatly improved.
[0124] The above results show that the sandwich structure MXene / AgNWs / MXene flexible transparent conductive electrode has low roughness and good mechanical flexibility, laying the foundation for its application in flexible OLEDs.
[0125] Application Example 2
[0126] To further demonstrate the feasibility of the sandwich structure flexible transparent conductive electrode of the present invention as an electrode material, this application example uses Example 6 to prepare a sandwich structure flexible transparent conductive electrode as an anode, and Ir(ppy)3 is doped in the main material as a green light emitting material to prepare a green OLED phosphorescent device with the following device structure: MXene / AgNWs / MXene / MoO3 (3nm) / TAPC (100nm) / TCTA:Bepp2:Ir(ppy)3 (1:1:6wt% 20nm) / TPBi (45nm) / LiF (1nm) / Al (100nm).
[0127] Among them, MXene / AgNWs / MXene is used as the anode, MoO3 as the hole injection layer, TCTA as the hole transport layer, TCTA:Bepp2:Ir(ppy)3 (1:1:6 wt%) as the phosphorescent organic light-emitting layer, TPBi as the electron transport layer, LiF as the electron injection layer, and Al layer as the cathode.
[0128] Furthermore, the commercial flexible PET-ITO conductive film in Application Example 1, and the P-AgNWs, MXene / AgNWs and AgNWs / MXene prepared in Examples 3 to 5 were used as anodes to replace MXene / AgNWs / MXene, and green phosphorescent OLED devices with the same structure were prepared for comparison.
[0129] Fig.10 The normalized electroluminescence spectra (a), current efficiency-voltage-brightness curves (b), external quantum efficiency-brightness curves (c) and current efficiency-brightness curves (d) of the above-mentioned various devices are given.
[0130] The luminescence spectrum in (a) shows that all five OLED devices achieve green light emission of 512nm, and different anode materials have little effect on the luminescence wavelength of the device.
[0131] Furthermore, according to the external quantum efficiency-brightness curve of (c) and the current efficiency-brightness curve of (d), it can be seen that the maximum external quantum efficiencies of ITO, P-AgNWs, MXene / AgNWs, AgNWs / MXene and MXene / AgNWs / MXene are 21.3%, 14.7%, 17.6%, 21.2% and 22.9%, respectively, and the current efficiencies are 73.4 cd / A, 53.9 cd / A, 62 cd / A, 73.8 cd / A and 81.4 cd / A, respectively. The sandwich-structured MXene / AgNWs / MXene flexible transparent conductive electrode has the highest device efficiency, and the maximum current efficiency is 1.1 times that of the ITO-based OLED.
[0132] Moreover, the device performance of the sandwich-structured flexible transparent conductive electrode OLEDs is also better than that of other OLEDs based on AgNWs flexible transparent conductive electrodes, and the efficiency roll-off of this green flexible OLED is very small. For example, as the brightness increases to 2027 cd m - ², CE and EQE still reach 76.3cd A -1 and 21.5%, and the current efficiency only decreased by 5%.
[0133] like Fig.11 As shown in the figure, green hole-only devices (HOD): substrate / MoO3 / TAPC / TCTA: Bepp2: Ir(ppy)3 / Al and electron-only devices (EOD): ITO / TCTA: Bepp2: Ir(ppy)3 / TPBi / LiF / Al were further prepared, and the charge balance analysis of green OLEDs using various flexible transparent conductive electrodes (FTCEs) was performed through the JV curves of the corresponding single-hole and single-electron devices. All functional layers and thicknesses in the above single-carrier devices are consistent with the above green phosphorescent OLED devices.
[0134] from Fig.11 It can be seen that under the same driving voltage, the MXene / AgNWs / MXene flexible transparent conductive electrode has the highest hole current density, and its single electron device is almost completely matched with the single hole device, which means that the flexible OLEDs based on MXene / AgNWs / MXene have very good charge balance in the EML region, which is the basic reason for the target device to achieve high efficiency.
[0135] Application Example 3
[0136] A sandwich structure flexible transparent conductive electrode was prepared in Example 6 as the anode, and Ir-RD was doped into the main material as a red light-emitting material to prepare a red OLED phosphorescent device having the following device structure: MXene / AgNWs / MXene / MoO3(3nm) / TAPC (100nm) / TCTA:Bepp2:Ir-RD (1:1:4wt% 20nm) / TPBi (45nm) / LiF(1nm) / Al (100nm).
[0137] In the above device, MXene / AgNWs / MXene is the anode; MoO3 is the hole injection layer; TCTA is the hole transport layer; TCTA:Bepp2:Ir-RD (1:1:4wt%) is the phosphorescent organic light-emitting layer; TPBi is the electron transport layer; LiF is the electron injection layer; and Al is the cathode.
[0138] The commercial flexible PET-ITO conductive film of Application Example 1 and the P-AgNWs, MXene / AgNWs and AgNWs / MXene of Examples 3 to 5 were used to replace the sandwich structure flexible transparent conductive electrode as the anode, and red phosphorescent OLED devices of the same structure were prepared for comparison.
[0139] Fig.12 The normalized electroluminescence spectra (a), current efficiency-voltage-brightness curves (b), external quantum efficiency-brightness curves (c) and current efficiency-brightness curves (d) of the above-mentioned various devices are given.
[0140] The luminescence spectrum in (a) shows that all five OLED devices achieve red light emission, and different anode materials have little effect on the luminescence wavelength of the device.
[0141] In terms of red flexible OLEDs, all OLEDs based on AgNWs flexible transparent conductive electrodes showed a low turn-on voltage of 2.8 V. Furthermore, according to the external quantum efficiency-luminance curve (c) and the current efficiency-luminance curve (d), the sandwich structure MXene / AgNWs / MXene flexible transparent conductive electrode achieved the highest device efficiency, with the maximum external quantum efficiency and current efficiency reaching 24.6% and 28.4 cd / A, respectively, which is better than P-AgNWs (13.9%, 16.8 cd / A), MXene / AgNWs (20.1%, 24 cd / A), AgNWs / MXene (23.4%, 27 cd / A) and ITO (21.2%, 20.5 cd / A).
[0142] It is noteworthy that the EQE-brightness characteristics of the above red flexible OLEDs remain stable until reaching very high brightness (260 cd m -2 23.3% at 2144 cd m -2 The efficiency roll-off is significantly lower (23.1%), which is an excellent comprehensive performance.
[0143] The red HOD: substrate / MoO3 / TAPC / TCTA: Bepp2: Ir-RD / Al and EOD: ITO / TCTA: Bepp2: Ir-RD / TPBi / LiF / Al were prepared in the same way, and all functional layers and thicknesses in the single carrier device were consistent with the above-mentioned red phosphorescent OLED device.
[0144] from Fig.13 It can be seen that under the same driving voltage, all AgNWs-based devices show relatively higher current density, indicating that the AgNWs composite electrode has better hole injection ability. In addition, it is worth noting that the single-electron and single-hole devices of the MXene / AgNWs / MXene flexible transparent conductive electrode are almost completely matched, which means that the MXene / AgNWs / MXene flexible OLED has a very good charge balance in the EML region and the overall device performance is optimal.
[0145] The high device efficiency further proves the practicality of the sandwich-structured MXene / AgNWs / MXene flexible transparent conductive electrode. At the same time, the successful preparation of green and red light devices based on this electrode proves the universality of this electrode and provides a new method to replace ITO as a flexible transparent conductive electrode.
[0146] Note: The abbreviations and full names of the materials used in the OLED device are as follows:
[0147] TCTA: 4,4`,4`-Tris(carbazoyl-9-yl)-triphenylamine
[0148] TAPC: 1, 10-bis-(di-4-tolylaminophenyl)cyclohexane
[0149] Bepp2:bis[2-(2-hydroxyphenyl)-pyridine]beryllium
[0150] Ir(ppy)3:tris(2-phenylpyridine)iridium(Ⅲ)
[0151] Ir-RD: bis(2-(4,5-dimethylbenzena) quinoline-5-butyl)(acetylacetonate) iridium(III)
[0152] TPBi: 2,2`,2``-(benzene-1,3,5-triyl)-tri(1-phenyl-1 H-benzimidazole)
[0153] The above embodiments of the present invention do not describe all the details in detail, nor limit the present invention to the above embodiments. Various changes, modifications, substitutions and variations made by ordinary technicians in this field without departing from the principles and purpose of the present invention should be included in the protection scope of the present invention.
Claims
1. A sandwich structure flexible transparent conductive electrode is obtained by sequentially depositing a bottom MXene nanosheet film, an AgNWs film and a top MXene nanosheet film on a flexible transparent substrate through a solution film forming process to form a composite film, and subjecting the composite film to mechanical pressure treatment to obtain a sandwich structure MXene / AgNWs / MXene flexible transparent conductive electrode.
2. The flexible transparent conductive electrode according to claim 1, characterized in that The flexible transparent substrate is any one of polyethylene terephthalate, low-density polyethylene, polyethylene naphthalate, polyimide or polydimethylsiloxane.
3. The flexible transparent conductive electrode according to claim 1, characterized in that The mechanical pressure treatment is to apply an external pressure of 1 to 50 MPa to the composite film.
4. The method for preparing the sandwich structure flexible transparent conductive electrode according to claim 1, comprising: S1: Depositing a MXene dispersion on a flexible transparent substrate, and performing annealing treatment at an annealing temperature higher than the sublimation temperature of the MXene dispersion to construct an underlying MXene nanosheet film; S2: Continue to deposit the AgNWs dispersion on the bottom MXene nanosheet film, and perform annealing at an annealing temperature higher than the sublimation temperature of the AgNWs dispersion to form an AgNWs film; S3: Continue to deposit MXene dispersion on the AgNWs film, and perform annealing at an annealing temperature higher than the sublimation temperature of the MXene dispersion to construct a top MXene nanosheet film; S4: Applying a pressure of 1 to 50 MPa to the prepared composite film for mechanical pressure treatment to prepare a sandwich structure MXene / AgNWs / MXene flexible transparent conductive electrode.
5. The preparation method according to claim 4, characterized in that The MXene dispersion or the AgNWs dispersion is deposited by solution spin coating or solution spray coating.
6. The preparation method according to claim 4, characterized in that The annealing treatment time is 1 to 60 minutes.
7. The preparation method according to claim 4, characterized in that The MXene dispersion or the AgNWs dispersion is a dispersion prepared by using a solvent having a polarity similar to that of MXene or AgNWs.
8. The preparation method according to claim 7, characterized in that The solvent with similar polarity is a single solvent or a mixed solvent composed of two or more solvents.
9. Use of the sandwich structure flexible transparent conductive electrode according to claim 1 as an electrode material in the preparation of a flexible organic light-emitting diode device.
10. Use of the sandwich structure flexible transparent conductive electrode according to claim 1 in the preparation of solar cells and photoelectric detection devices.